Economic impacts of water market simulation in agriculture - Leyla Nourani; Seyed Nematolla Moosavi; Abdoulrasool Shirvanian (Water Supply, 2022)
Water market is one of the modern issues in demand management in face of water scarcity, which is increasingly used in different parts of the world as a tool for optimal allocation of water consumption and transfer of water to consumers with higher final efficiency. Despite the benefits of forming a water market, such markets are not yet developed in developing countries, such as Iran. Accordingly, this study examines the economic impact of water market design on farmers’ livelihood in Iran. The data of this study were collected using a multistage random sampling method from 100 users with water rights in the irrigation network of Ramjerd plain in Fars province. The data were analyzed using positive mathematical programming and scenario making. The results showed that with the formation of the water market, the gross margin of the total lands with irrigation network of Ramjerd plain increased from 2,013.080 billion Rials to 2,194.2200 billion Rials. As a result, the agricultural economic situation of the region experienced an increase of 9%. therefore an appropriate legal and regulatory structure is recommended to create a water market on the lands located within the irrigation networks. HIGHLIGHTS Comprehensive assessment of the effects of water market design on farmers’ gross margin and crop pattern by region.; Application of positive mathematical programming to simulate the effects of water market formation on economic situation of farmers.; In terms of water transfer costs in order to make the effects of water market policy more realistic.;